Back to the future, forward to the past: Croatian politics of memory in the European Parliament. Issue 5 (3rd September 2017) - Milošević, Ana
Abstract : This paper discusses the way in which a post-conflict European Union (EU) member immediately after accession both shapes and adapts to EU memory politics as a part of its Europeanization process. I will analyze how the country responds to the top-down pressures of Europeanization in the domestic politics of memory by making proactive attempts at exporting its own politics of memory (discourses, policies, and practices) to the EU level. Drawing evidence from Croatian EU accession, I will consider how Croatian members of the European Parliament "upload" domestic memory politics to the EU level, particularly to the European Parliament. Based on the analysis of elite interviews, discourses, parliamentary duties, agenda-setting, and decision-making of Croatian MEPs from 2013 to 2016, I argue that the parliament serves both as a locus for confirmation of European identity through promotion of countries' EU memory credentials and as a new forum for affirmation of national identity. The preservation of the "Homeland War" narrative (1991–1995) and of the "sacredness" of Vukovar as a European lieu de mémoire clearly influences the decision-making of Croatian MEPs, motivating inter-group support for policy building and remembrance practices that bridge domestic political differences.